2011
DOI: 10.2174/2210289201102010080
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of Trigonelline and 4-Hydroxyisoleucine with Hypoglycemic Activity in Cell Suspension Cultures of Trigonella foenum graecum L

Abstract: Cell suspension cultures of Trigonella foenum graecum L. (fenugreek) were initiated from the cotyledon portions of sterile germinated seeds and maintained on MS medium supplemented with 2, 4-dichlorophenoxy acetic acid (2, 4-D) (1mg/l), kinetin (0.1 mg/l) and sucrose (5%). The changes in cell mass and both trigonelline and 4-hydroxyisoleucine content were followed between days zero and 12. The linear increase in fresh weight was found to be parallel to both trigonelline and 4-hydroxyisoleucine production. Cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The important constituents of fenugreek include 4-hydroxyisoleucine (4-HI), trigonelline, galactomannan flavonoids, carotenoids, coumarins, proteins, saponins and lipids (Basch, Ulbricht, Kuo, Szapary, & Smith, 2003). Trigonelline controls the diabetes through operation of the mechanism of insulin secretion, modulation of β cell regeneration and stimulation of activity of glucose metabolism-related enzymes (Abd El-Mawla & Osman, 2011;Zhou, Chan, & Zhou, 2012). The seeds of fenugreek contain about 50% of fibre that is known to slow the rate of post-parandial glucose absorption, which may be responsible for the hypoglycaemic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The important constituents of fenugreek include 4-hydroxyisoleucine (4-HI), trigonelline, galactomannan flavonoids, carotenoids, coumarins, proteins, saponins and lipids (Basch, Ulbricht, Kuo, Szapary, & Smith, 2003). Trigonelline controls the diabetes through operation of the mechanism of insulin secretion, modulation of β cell regeneration and stimulation of activity of glucose metabolism-related enzymes (Abd El-Mawla & Osman, 2011;Zhou, Chan, & Zhou, 2012). The seeds of fenugreek contain about 50% of fibre that is known to slow the rate of post-parandial glucose absorption, which may be responsible for the hypoglycaemic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Fowden et al (1973) isolated and identified the amino acid, 4hydroxyisoleucine, in fenugreek seed for the first time. AbdelMawla and Osman (2011) used cell suspension cultures to raise the con centration of 4hydroxyisoleucine content in fenugreek seed, which increased serum insulin levels and showed improvement in lowering the fasting blood glucose level in streptozotocin (STZ)treated diabetic rats. AbdelMawla and Osman (2011) used cell suspension cultures to raise the con centration of 4hydroxyisoleucine content in fenugreek seed, which increased serum insulin levels and showed improvement in lowering the fasting blood glucose level in streptozotocin (STZ)treated diabetic rats.…”
Section: The Alkaloid-trigonellinementioning
confidence: 99%
“…The induction effect of both MJ and Q can be suppressed by pre-incubation of hairy root cultures with salicylic acid. Both Trigonelline and 4-Hydroxyisoleucine ( Figure 11) with Hypoglycemic Activity were elicited in Cell Suspension Cultures of Trigonella foenum graecum L. [128]. Cell suspension cultures of Trigonella foenum graecum L. (fenugreek) were initiated from the cotyledon portions of sterile germinated seeds and maintained on MS medium supplemented with 2, 4-dichlorophenoxy acetic acid (2, 4-D) (1mg L -1 ), kinetin (0.1 mg L -1 ) and sucrose (5%).…”
Section: Cardiac Glycosides From Cryptostegiamentioning
confidence: 99%